Comparison of Physical Literacy and Upper Extremity Functions in Girls With and Without Upper Crossed Syndrome - zahra khosravi; Ebrahim Mohammad Ali Nasab Firouzjah; Morteza Homayounnia Firouzjah (University of Tehran, 2023)
Introduction: Upper crossed syndrome causes movement limitation and weakness in people's movement functions. This study aimed to compare physical literacy and upper extremity movement functions in girls with and without the upper crossed syndrome.Methods: The method of this research was descriptive and causal-comparative using field data collection. The statistical population of the research included two groups of healthy 10- to 12-year-old female students and also students with the upper crossed syndrome in Khalkhal City in the academic year of 2022-2023. Using G-power software, the statistical sample size was determined to be 60 people. These people were screened using a checkerboard and after quantitative height assessment, they were assigned to two Healthy (30 people) and the Upper Cross Syndrome (30 people) groups. Forward head angle and forward shoulder angle were measured using photography, kyphosis angle was measured using the Goniometer-pro app. The Canadian Assessment of Physical Literacy - version 2 (CAPL-2) questionnaire was used for the evaluation of physical literacy and Upper Quarter Y-Balance Test (UQYBT) was used to assess upper limb function. The Data were analyzed using an independent t-test in SPSS-26 software at the significant level of 0.05.Results The results showed that healthy girls were significantly in a better condition in all variables of physical literacy and upper limb function than girls with the upper crossed syndrome.Conclusion: According to the results of this research, it is suggested that coaches and sports and health professionals use the results of this study to develop the physical literacy and functions of students with the upper crossed syndrome.